Metalaxyl Resistance of Phytophthora palmivora Causing Durian Diseases in Thailand - Pornprapa Kongtragoul; Koichiro Ishikawa; Hideo Ishii (My University, 2021)
Thailand is the leading producer and exporter of durians worldwide. Serious diseases in durians include root rot, stem rot, and fruit rot, which are caused by Phytophthora palmivora, P. nicotianae, and Pythium cucurbitacearum, respectively. Thai farmers have applied fungicides for more than 20 years to control rot, but it remains difficult to control. Thus, the monitoring of fungicide-resistance development in pathogens is important for disease management. Pathogens were isolated from naturally infected durians between 2016 and 2017 in southern Thailand. The sequences of the internal transcribed spacer (ITS) and 5.8S regions of rDNA were used for the identification of their species. Seventeen out of twenty isolates were confirmed to be P. palmivora. All the isolates were tested for mycelium-growth sensitivity to metalaxyl, azoxystrobin, and dimethomorph. The results showed that nine isolates were resistant to metalaxyl with the 50% effective concentration (EC50) higher than 100 mg L−1. By contrast, all the isolates were sensitive to both azoxystrobin and dimethomorph, with EC50 < 1 mg L−1. Metalaxyl-resistant isolates were not controlled (−25.6% to 22.2%) by the treatment of the detached leaves of ‘Monthong’ durian with 100 mg L−1 metalaxyl prior to inoculation, but all the metalaxyl-sensitive and moderately metalaxyl-resistant isolates were better controlled (33.0% to 62.6%). These results clearly indicate that metalaxyl-resistant strains are present in the populations of P. palmivora in Thailand.
Keywords: Metalaxyl; Phytophthora palmivora; Plant Pathogens and Resistance